(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
This article studied lipid metabolism in patients with type 2 diabetes. Against the background of decompensation, diabetic dyslipidemia was detected in the examined patients, with an increase in total cholesterol, triglycerides, and atherogenic fractions of low-density lipoproteins, as well as a decrease in high-density lipoproteins. At the same time, a relationship was revealed between the content of lipoproteins of various classes with duration and BMI of patients. An analysis was conducted between monotherapy and monotherapy for diabetic dyslipidemia. Rosuvastatin 10 mg/ day and the fixed drug rosuvastatin + ezetimibe at a dose of 10/10 mg/ day. A combination therapy of rosuvastatin and ezetimibe 10/10 mg is an effective drug for the treatment of diabetic dyslipidemia.